1994
DOI: 10.1021/bi00206a034
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Adsorption and Aggregation Associated Changes in Secondary Structure of Human Calcitonin Monitored by ATR-FTIR Spectroscopy

Abstract: The peptide hormone human calcitonin (hCT) has a marked tendency to aggregate in aqueous solutions, resulting in viscous and turbid dispersions consisting of long fibrils approximately 80 A in diameter. Both transmission (T-FTIR) and attenuated total reflection Fourier transform infrared (ATR-FTIR) experiments were applied on hCT adsorption and aggregation kinetics. By means of the surface sensitive ATR-FTIR spectroscopy at a hydrophobic/hydrophilic interface, early adsorption and aggregation steps of hCT coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
59
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 25 publications
7
59
0
Order By: Relevance
“…In sarcoplasmic reticulum Ca 2+ -ATPase, the helix position was assigned at 1645 cm -1 . Helical bands in calcinotin were assigned at 1637 cm -1 (43) and in alanin-based peptides as low as 1632-1635 cm -1 (44). In the same spectral region, R-helical bands (additional to bands at the classical position) of apolipoprotein fragments have been proposed (45).…”
Section: Discussionmentioning
confidence: 88%
“…In sarcoplasmic reticulum Ca 2+ -ATPase, the helix position was assigned at 1645 cm -1 . Helical bands in calcinotin were assigned at 1637 cm -1 (43) and in alanin-based peptides as low as 1632-1635 cm -1 (44). In the same spectral region, R-helical bands (additional to bands at the classical position) of apolipoprotein fragments have been proposed (45).…”
Section: Discussionmentioning
confidence: 88%
“…The coiled-coil proteins analyzed in this study (see above) provide an additional example of band shift. Recently, the R-helical band of calcitonin was empirically assigned to 1637 cm -1 (Bauer et al, 1994) and in alanine-based peptides the helical band occurs in the range between 1632 and 1635 cm -1 (Matinez & Milhauser, 1995). One possible explanation for the shift of R-helical bands toward lower wavenumbers could be a distortion in the helices as discussed above.…”
Section: Coiled-coil Proteins Have a Unique Ftir Spectrummentioning
confidence: 99%
“…Amyloid fibrils composed of hCT were found to be associated with medullary carcinoma of the thyroid (17)(18)(19). It was also found that synthetic hCT can form amyloid fibrils in vitro with a similar morphology to the deposits found in the thyroid (17)(18)(19)(20)(21)(22)(23). The in vitro process of amyloid formation is affected by the pH of the medium (23).…”
mentioning
confidence: 99%
“…However, studies of hCT fibrils using circular dichroism, fluorescence, and infrared spectroscopy revealed that fibrillated hCT molecules have both ␣-helical and ␤-sheet secondary structure components (21). NMR spectroscopy studies have shown that in various structure-promoting solvents like trifluoroethanol/H 2 O, hCT adopts an amphiphilic ␣-helical conformation predominantly in the residue range of 8 -22 (24 -25).…”
mentioning
confidence: 99%